Remembering John/Ivan Demjanjuk: Inclusive and exclusive frames in cosmopolitan holocaust discourse - Christian Pentzold; Vivien Sommer (International Communication Gazette, 2021)
This article analyzes the media representations circulating around the trials of the accused Nazi collaborator John/Ivan Demjanjuk. It examines the American, Dutch, German, Russian, Jewish-Dutch, and Jewish-American discourses that framed the consecutive legal proceedings in Israel, the U.S., and Germany. Our study interrogates the convergences and divergences in the transcultural translations as well as the local appropriations of the events that formed part of the cosmopolitan remembrance of the Holocaust. We reconstructed inclusive media frames which were able to traverse different languages and cultures. We also found exclusive frames in our study that did not travel across these boundaries. The palette of views on Demjanjuk's personal guilt and on the capacity of the trials were informed by culturally restricted or culturally resonative mnemonic tropes and were sponsored by different groups of memory agents.
Keywords: 300; Cosmopolitan memory; Demjanjuk; Holocaust; media frames; media memory; qualitative frame analysis